Corruption as negative social phenomenon (Journal of actual problems of jurisprudence, 2019)
Kazakhstan realizes, that the corruption brakes process of socio economic development, construction of marketeconomy, of attraction of the investments and negatively influences political and public institutes of the democraticstate, represents serious threat to the future development of the country.The general(common) control of realization of the Program will be carried out by Administration of the President ofRepublic of Kazakhstan.For execution(performance) of measures on realization of the Program the Government of Republic of Kazakhstan can create interdepartmental groups, which should represent the reports to target dates and will bear responsibility for theirqualitative and duly performance.At the second stage (2009-2010 years): growth of activity of not governmental organizations, political parties(sets) andpublic associations in realization anticorruption of politics; creation of conditions for the further growth of economyand improvement of an investment climate; expansion of the international cooperation in the field of struggle withcorruption; strengthening of prestige of the state on the international arena.Key words: that the corruption brakes process of socio economic development, struggle with offences in sphere ofeconomy, expansion of the international cooperation in the fi eld of struggle with corruption.